2015
DOI: 10.1038/bjc.2014.664
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear osteopontin-c is a prognostic breast cancer marker

Abstract: Background:Although Osteopontin has been known as a marker for cancer progression, the elevated production of this cytokine is not specific for cancer. We have identified the splice variant Osteopontin-c as being absent from healthy tissue but associated with about 75% of breast cancer cases. However, in previous studies of Osteopontin-c, follow-up information was not available.Methods:Here we have analysed 671 patients, comprising a cohort of 291 paraffin blocks plus a population-based case-control study of 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 25 publications
0
34
0
1
Order By: Relevance
“…The reactivity of the autoantibodies was consistent with the appearance of splice variants in individual cancers. Breast cancer expresses OPN-a and -c, but not OPN-b (15,19,20). Liver cancer has elevated levels of OPN-a and -b, but not -c (14).…”
Section: Discussionmentioning
confidence: 99%
“…The reactivity of the autoantibodies was consistent with the appearance of splice variants in individual cancers. Breast cancer expresses OPN-a and -c, but not OPN-b (15,19,20). Liver cancer has elevated levels of OPN-a and -b, but not -c (14).…”
Section: Discussionmentioning
confidence: 99%
“…After deparaffinization of sections with xylene, they were rehydrated in graded ethanol series (80%, 90%, 95%, and three 100%) and immersed in 0.3% hydrogen peroxide in methanol for 30 minutes at room temperature to block endogenous peroxidase activity. In the next step, for antigen retrieval, sections were incubated with retrieval solution ( [16], and the intensity score (IS) and proportional score (PS) were calculated and reported [17]. The IS was given as follows: 0= No positively stained cell or weak staining, 1= moderate staining, and 2=strong staining [17].…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…In contrast, OPN-a promoted cell adhesion (64). A follow up study with increased number of patient samples found a more complex picture, but demonstrated strong association between nuclear OPN-c and mortality in patients with early onset breast cancer, while expression of OPN-a/b in the cytoplasm was associated with poor prognosis (68). In pancreatic cancer the picture is subtly different.…”
Section: Osteopontin Splice Variantsevidence For Association With Spementioning
confidence: 99%